2008
DOI: 10.1103/physrevlett.100.183401
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Charge Transfer and Fragmentation Cross Sections inHe2+C60Collisions

Abstract: We have determined absolute charge transfer and fragmentation cross sections in He2++C60 collisions in the impact-energy range 0.1-250 keV by using a combined experimental and theoretical approach. We have found that the cross sections for the formation of He+ and He0 are comparable in magnitude, which cannot be explained by the sole contribution of pure single and double electron capture but also by contribution of transfer-ionization processes that are important even at low impact energies. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…The form of the distribution shown in Fig. 2 is qualitatively similar to those obtained by fitting theoretical fragmentation probabilities to experimental measured branching ratios in small carbon clusters [27] and fullerenes [33,35], in which the energy distribution was the fitting parameter, thus showing that the present results are also compatible with previous empirical estimations. Notice that, although the set of accessible target states can, in principle, be different in photoionization and collision processes, due to the different conservation rules that can apply in each case, this is not a problem in the present work because the absence of any symmetry in the molecular target does not restrict the number of accessible states in either process.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…The form of the distribution shown in Fig. 2 is qualitatively similar to those obtained by fitting theoretical fragmentation probabilities to experimental measured branching ratios in small carbon clusters [27] and fullerenes [33,35], in which the energy distribution was the fitting parameter, thus showing that the present results are also compatible with previous empirical estimations. Notice that, although the set of accessible target states can, in principle, be different in photoionization and collision processes, due to the different conservation rules that can apply in each case, this is not a problem in the present work because the absence of any symmetry in the molecular target does not restrict the number of accessible states in either process.…”
supporting
confidence: 88%
“…Collisions at closer impact parameters can explain the extended tail towards larger deposited energy [27,32,33]. Penetrating trajectories are associated with large deposit energy of several tens of eV [33]. However, in the present interaction of 48 keV O 6þ with thymidine, peripheral collisions leading to small energy transfer are dominating.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…C 2 emission from C q+ 60 is found to dominate when q 2 while C + 2 emission dominates when q 5, in agreement with the present and previous experimental results. DOI Over the past decades, fullerenes have been extensively studied by means of various excitation and ionization agents, such as photons [1][2][3], electrons [4][5][6][7][8], ions [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], or laser pulses [25][26][27][28][29][30]. It has been demonstrated that hot fullerene ions produced in these interactions may cool down by electron emission [29,[31][32][33], radiative decay [34,35], or by statistical fragmentation processes [36][37][38][39].…”
mentioning
confidence: 99%